Salt‐Induced Flocculation of Dissolved Organic Matter and Iron Is Controlled by Their Concentration and Ratio in Boreal Coastal Systems. Issue 11 (10th November 2022) - Khoo, Celyn L. L.; Sipler, Rachel E.; Fudge, Alexandria R.; Beheshti Foroutani, Maryam; Boyd, Sean G.; Ziegler, Susan E.
Abstract: Rivers and estuaries are important conduits and reactors for organic matter (OM). Despite the substantial export of terrestrial OM by rivers, only a small proportion of this material reaches the open ocean. One potentially important mechanism contributing to the removal of terrestrial dissolved OM (DOM) is flocculation; a process that transforms DOM into larger size fractions that can settle into sediment pools. Here we investigate the role of flocculation in adjacent boreal coastal systems over three consecutive seasons. Flocculation experiments, which include the artificial salting of freshwater DOM to mid (12 psu) and high salinity (25 psu), and a 1:1 mixture of freshwater DOM with their respective saline endmember, highlight a potentially important source of particulate carbon (PC) in boreal estuaries. Along with a 3.5% ± 1.0% removal of dissolved organic carbon (DOC) and 44% ± 16% dissolved iron (DFe), the potential for flocculation of these constituents significantly increased with increasing salinity from 12 to 25 psu. The particulate matter (PM) produced by salt‐induced flocculation was comparable to in situ PC concentrations (in situ PC = 27.5 μmol L −1 and flocculated PC = 15.0 μmol L −1 ) and stable carbon isotopic signatures (in situ PM = −28.8‰ and flocculated PM = −28.3‰). DFe:DOC and Sr were the only parameters that could significantly explain the degree of carbon and iron flocculation. This demonstrates the importance of DOC, DFe, and optical properties, and the predictive value of DFe:DOC for understanding DOM susceptibility to flocculation and its relevance and contribution to regional and global carbon budgets. Plain Language Summary: The salt in seawater is an important factor shaping the transport, transformation, and fate of organic matter (OM) from rivers to the ocean. Salts can cause compounds to stick together and form larger particles in a process called flocculation. These larger particles can sink to the bottom where they can be effectively stored in sediments; however, understanding the factors behind how much and where flocculation may occur is still unresolved. Bridging these knowledge gaps will contribute to improved landscape and regional carbon budgets. We investigated the impact of flocculation in two boreal coastal systems using a series of laboratory experiments across multiple seasons. Our findings highlight the important contribution of flocculation in removing OM from the water column. Flocculation can occur across the entire range of estuarine salinities while the degree to which it contributes to particulate OM at a given salinity is dependent upon dissolved OM quantity, source, and composition. We further show flocculation to be a selective process, whereby the concentration of iron and organic carbon, as well as their ratio, can be a useful tool to predict the degree of flocculation at regional scales. Key Points: Flocculation affects dissolved and particulate organic matter and iron distribution and characteristics; thus is a requisite for carbon flux estimates Dissolved organic carbon, dissolved iron, and their molar ratio are useful predictors of the spatial and temporal variations in flocculation Salt‐induced flocculation can occur in salinities up to 25 psu